2008
DOI: 10.1029/2008gl035376
|View full text |Cite
|
Sign up to set email alerts
|

Determination of day‐time OH emission heights using simultaneous meteor radar, day‐glow photometer and TIMED/SABER observations over Thumba (8.5°N, 77°E)

Abstract: [1] Simultaneous day-glow photometer and meteor radar observations are used for determining the day-time OH emission height for the first time over Thumba (8.5°N, 77°E). The meteor radar observations are extensively used to obtain the ambipolar diffusion coefficient (D a ) profile in the 82-98 km height region and are compared with OH rotational temperature (TOH) measurements. The height profile of correlation coefficient between D a and TOH showed a maximum at 90 km. These ground based estimates are then com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The DGPM temperature measurements over Thumba agreed reasonably well with those obtained from collocated meteor radar, but for a very short period of time (summer equinox) (Vineeth et al 2005). It was also noticed that the OH-dayglow temperature measurements depended on the OH-emission height, which may vary with seasons (Takahashi et al 2005, Kumar et al 2008). In addition, the temporal variation of OH-emission heights showed tidal modulation.…”
Section: Multi-wavelength Dayglow Photometermentioning
confidence: 57%
“…The DGPM temperature measurements over Thumba agreed reasonably well with those obtained from collocated meteor radar, but for a very short period of time (summer equinox) (Vineeth et al 2005). It was also noticed that the OH-dayglow temperature measurements depended on the OH-emission height, which may vary with seasons (Takahashi et al 2005, Kumar et al 2008). In addition, the temporal variation of OH-emission heights showed tidal modulation.…”
Section: Multi-wavelength Dayglow Photometermentioning
confidence: 57%
“…Takahashi et al (2005) reported OH emission heights deduced from cross correlating rotational temperatures from the OH(6-2) band and meteor trail ambipolar diffusion coefficients at Shigaraki (35 • N, 136 • E). Kumar et al (2008) employed a similar technique to infer day-time emission heights over Thumba (8.5 • N, 77 • E) which corresponded well with peak heights observed in SABER OH VER profiles in the same time period. Liu and Shepherd (2006) found that, in the latitude range 40 • S to 40 • N, the altitude of the peak of the OH layer is almost completely described by the integrated emission rates (IER) in their study of WINDII profiles from the UARS satellite.…”
Section: Introductionmentioning
confidence: 93%
“…So the height distribution of the emission layer would indirectly affect the measured OH temperature. The temperature has shown to have a negative correlation with the OH height [Kumar et al, 2008]. Similarly, the mesopause altitude has also shown to have a negative correlation with the mesopause temperature [Friedman, 2003].…”
Section: Variability Of Daytime Mesopause Temperature During the Daymentioning
confidence: 95%
“…This may be because of a multitude of reasons including the seasonal variation in the OH layer height and the mesopause altitude. However, a study carried out by Kumar et al [2008] during the February to March 2005 period showed that the OH layer is located at around 90 km over Trivandrum. Therefore, more comprehensive analysis is required to quantify this aspect and will be attempted in future.…”
Section: Seasonal Variabilitymentioning
confidence: 99%